If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2y + -2) = 7y + -21 Reorder the terms: 3(-2 + 2y) = 7y + -21 (-2 * 3 + 2y * 3) = 7y + -21 (-6 + 6y) = 7y + -21 Reorder the terms: -6 + 6y = -21 + 7y Solving -6 + 6y = -21 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. -6 + 6y + -7y = -21 + 7y + -7y Combine like terms: 6y + -7y = -1y -6 + -1y = -21 + 7y + -7y Combine like terms: 7y + -7y = 0 -6 + -1y = -21 + 0 -6 + -1y = -21 Add '6' to each side of the equation. -6 + 6 + -1y = -21 + 6 Combine like terms: -6 + 6 = 0 0 + -1y = -21 + 6 -1y = -21 + 6 Combine like terms: -21 + 6 = -15 -1y = -15 Divide each side by '-1'. y = 15 Simplifying y = 15
| 7/2,5=25/x | | -2(5s-1)-2=-2(9s+1)-3 | | 7/2,5=25x | | 7/2,5=25/y | | 3(x-1)=6x+7 | | y-14y^3-y^5= | | y-14y^3-y^5/y= | | 2+4x+2=0 | | (3y+2)-9=y-9 | | (3y-2)-9=y-9 | | (3b-5)(4b+1)= | | 10.5*(3(15-1)2+3(15-1)+1)=x | | 10.5*(3(15-1)2+3(15-1)+1)= | | 5*(3(15-1)2+3(15-1)+1)=X | | 7m-12=-33 | | 8x+4-2=26 | | -5x^2-4x+2=0 | | (2-2y)*((2-x)/2)=0 | | -3(8p+4)-2(1-23p)=3(6+7p) | | (2-2y)*((2-x)/2) | | x=1.01255555555555 | | 2-2y+2y-2=0 | | x=-1.01255555555555 | | 7/5x-10=3 | | 6[x+4(2-x)]=3x+1 | | 5t^2+2t+0.1=0 | | 3x+7-5(x+1)=5x+7 | | 4/3(3.14)(11)3 | | P=pr^2+prs | | .07x=1400 | | 0.7x=1400 | | (11b-2)-5(2b+1)=-7 |